“Whych in Aragon was doon”: Re-evaluating the Setting of the Croxton Play of the Sacrament - Atiya, Alexandra (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2026)
Scholars have analyzed the Croxton Play of the Sacrament, a medieval English host desecration play, primarily from an English perspective, even though the play is set in Aragon and its banns and colophon claim Mediterranean origins. This paper argues these paratexts present the play as a product of interregional travel and create parallels between literary and commercial exchange. Exploration of a manuscript note that erroneously attributes the play to a Spanish playwright reinforces this point. English and Iberian sources reveal how the Croxton play’s dual setting shapes its central themes of trade, conversion, and inter-religious conflict.